Formant frequencies of Malay vowels produced by Malay children aged between 7 and 12 years. - Ting, H.N.; Zourmand, A.; Chia, S.Y.; Yong, B.F.; Abdul Hamid, B. (Elsevier, 2012)
The formant frequencies of Malaysian Malay children have not been well studied. This article investigates the first four formant frequencies of sustained vowels in 360 Malay children aged between 7 and 12 years using acoustical analysis. Generally, Malay female children had higher formant frequencies than those of their male counterparts. However, no significant differences in all four formant frequencies were observed between the Malay male and female children in most of the vowels and age groups. Significant differences in all formant frequencies were found across the Malay vowels in both Malay male and female children for all age groups except for F4 in female children aged 12 years. Generally, the Malaysian Malay children showed a nonsystematic decrement in formant frequencies with age. Low levels of significant differences in formant frequencies were observed across the age groups in most of the vowels for F1, F3, and F4 in Malay male children and F1 and F4 in Malay female children.